METHODOLOGY OF TEACHING CHEMISTRY IN SCHOOLS BASED ON THE "5E" AND "4K" LEARNING MODELS (Web of Teachers: Inderscience Research, 2025)
This article analyzes the main approaches to organizing the current educational process. Specifically, it discusses the education policies of countries leading in modern education - such as Hong Kong, South Korea, Singapore, Japan, and Vietnam - which are rapidly rising in educational rankings. The paper examines documents that define educational standards and explores the most common competencies, values, attitudes, and other educational outcomes that should be developed in students. The role and distinctive features of the "5E" and "4K" learning models are highlighted, with attention given to the issues surrounding their application.